Congestion costs - Brems, Camilla Riff; Kristensen, Niels Buus; Sloth, Brigitte (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
Congestion costs have gained increased attention in the last couple of years. Among other things it is mentioned among the external costs that should be evaluated according to the European Commission's White Paper on European Transport Policy. This states, that "... the price for using the infrastructure should include both infrastructure costs and external costs, which include costs of accidents, emissions, noise and congestion. ..." This paper focuses on the effects of congestion on the road network. The paper presents a newly developed method to evaluate external costs of congestion including both increased travel times and increased variation in travel times. The method is applied to three different road segments in Copenhagen representing an urban road, an arterial road, and a motorway. It is demonstrated how the methods and its results can be used to analyse the levels and variation of congestion costs. The work presented here is part of a research project on Congestion, which is carried out by University of Copenhagen, Technical University of Denmark, the National Road Authorities, the Greater Copenhagen Development Council, the Municipality of Copenhagen and COWI. The project is financed by the Danish Transport Research Council and the Danish Ministry of Transport.